Dietary patterns as predictors of adverse antidiabetics reactions - A cross-sectional study of polish diabetes sufferers - Kornelia Skoczylas; Beata Babiarczyk; Anna Michalik (Journal of Education, Health and Sport, 2024)
Background: Diabetes mellitus (DM) is a multifaceted problem. There is a need to coordinate the diet with pharmacological interventions, because of the possible interaction between the two. The present study aimed to identify  the factors related to the dietary habits of people suffering with diabetes that may increase the  risk of adverse reactions to anti-diabetic medication.